A modified incremental gravitational search algorithm for short-term hydrothermal scheduling with variable head. (October 2020) - Yaşar, Celal; Özyön, Serdar
Abstract: In this study, the solution of short-term hydrothermal coordination problem (STHCP) with variable head was performed. In the manuscript, incremental gravitational search algorithm (IGSA) which was developed as a new method has been applied to two different power problems. One of the systems used as an example is a variable head STHCP which has previously been solved in the literature by neglecting transmission line losses. The second is a lossy system designed as a variable head STHCP, with the purpose of contributing to the literature. In the lossy system, Newton–Raphson AC power flow method was used to calculate transmission line losses. Possible electrical and hydraulic constraints in the solution of the problem were satisfied using the penalty function method. The results obtained from the solutions of the sample systems were compared and discussed. Highlights: The advantages of the incremental social learning structure (ISL) have been evaluated. New approach has been called Incremental gravitational search algorithm (IGSA). Short term hydrothermal coordination problem (STHCP) with variable head was studied. Two different example problems have been successfully solved with IGSA. IGSA has achieved acceptable results for the sample systems under consideration.